A qualitative study of reasons for seeking and ceasing opioid substitution treatment in prisons in New South Wales, Australia. (21st June 2016) - Larney, Sarah; Zador, Deborah; Sindicich, Natasha; Dolan, Kate
Abstract: Introduction and Aims: Opioid substitution treatment (OST) reduces drug‐related harms in custody and after release. However, OST providers in prisons have reported that some patients prefer to cease treatment prior to release, placing them at risk of fatal overdose. We aimed to examine reasons for seeking OST in custody, and intentions regarding continuation or cessation of treatment prior to and following release. Design and Methods: This qualitative study employed semi‐structured interviews with opioid‐dependent people currently incarcerated in New South Wales, Australia. Results: Of 46 participants, 27 were currently in OST. Reported benefits of OST included withdrawal management and avoidance of high‐risk injecting. Over a third of participants in OST stated their intention to withdraw from OST prior to release. Reasons included concerns that attending community OST clinics could lead to drug use or offending, family opposition, inconvenience of clinic attendance, stigma and a perception that prison provided an opportunity to withdraw from OST more easily than in the community. Nineteen participants had already ceased OST in custody or had declined it, citing preferences to 'be clean' and the long‐term nature of OST. Discussion and Conclusions: Balancing the preference of many patients to cease OST prior to release against patient safety post‐release is a substantial challenge for opioid treatment providers in correctional settings. These findings indicate the need for research on how best to attract and retain opioid‐dependent prisoners in treatment and the need to provide other interventions for prisoners uninterested in post‐release OST, such as take‐home naloxone. [Larney S, Zador D, Sindicich N, Dolan K. A qualitative study of reasons for seeking and ceasing opioid substitution treatment in prisons in New South Wales, Australia. Drug Alcohol Rev 2017;36:305–310]